Hubungan Antara Pengetahuan Dengan Efikasi Diri Penderita Tuberkulosis Paru - Herawati, Erni; Purwanti, Okti Sri (Jurnal Berita Ilmu Keperawatan, 2018)
Tuberculosis (TB) is a pulmonary infectious diseases that can attack the lungs. Handling of the high prevalence of TB should be taken to control the disease Pulmonary TB , one of which is the treatment. In addition to treatment to achieve a cure is very important for patients with pulmonary TB have the knowledge about the disease and have a high self-efficacy. The purpose of this study was to determine the relationship between knowledge and self-efficacy pulmonary tuberculosis patients. This research is quantitative research with a cross-sectional approach. The method used non-probability sampling. This research is pulmonary tuberculosis patients who underwent outpatient at Polyclinic BBKPM TB. The samples were 72 respondents with an accidental sampling technique. The instrument was a questionnaire of knowledge and self-efficacy has been tested on 20 patients with pulmonary tuberculosis. Non-parametric data analysis using the Spearman rho correlation coefficient test with the results showed that most of the patients are in the category of enough knowledge and most have high self-efficacy with p = 0.001 < Î± = 0.05 and Spearman correlation value for 0381. The conclusion that the existence of a positive and significant relationship between knowledge and self-efficacy pulmonary tuberculosis patients in Surakarta BBKPM.